2011
DOI: 10.1073/pnas.1017146108
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus type-35 vectors block human CD4 + T-cell activation via CD46 ligation

Abstract: Recombinant adenoviruses (rAds) based on types 5 (rAd5) and 35 (rAd35) have emerged as important vaccine delivery vectors in clinical testing for a variety of pathogens. A major difference between these vectors is their binding to cellular receptors used for infection. Whereas rAd5 binds coxsackie-adenovirus receptor (CAR), rAd35 binds the complement regulatory protein CD46. Although rAd35 infected and phenotypically matured human blood dendritic cells (DCs) more efficiently than rAd5, we show here that rAd35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Previous reports have characterized innate cytokine profiles of Ad vectors in mice (3,4,53) and in vitro (2,18,19,20,29,36,52). For example, several studies have reported that Ad35 induces higher levels of the costimulatory markers CD80 and CD40 and interferons than does Ad5 in vitro in human DC (29) as well as higher levels of IL-10 and reduced proliferation in T cells cocultured with DCs (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have characterized innate cytokine profiles of Ad vectors in mice (3,4,53) and in vitro (2,18,19,20,29,36,52). For example, several studies have reported that Ad35 induces higher levels of the costimulatory markers CD80 and CD40 and interferons than does Ad5 in vitro in human DC (29) as well as higher levels of IL-10 and reduced proliferation in T cells cocultured with DCs (2).…”
Section: Discussionmentioning
confidence: 99%
“…Vectors constructed using these viruses have been shown to differ significantly in terms of primary receptor usage (1,9,13,40,50), intracellular trafficking patterns (14,22,31,32), transduction and activation of dendritic cells (2,11,20,29,36,53), utilization of secondary receptors (15,48), cellular tropism (3,16,33,44,46,47), and interaction with pattern recognition receptors (PRR) (12,18,35). The species C adenovirus serotype 5 (Ad5), the species B2 adenovirus serotype 35 (Ad35), and the species D adenovirus serotype 26 (Ad26) are currently being evaluated as vaccine candidates in clinical trials, yet relatively little is known about the possible differences in innate immunity induced by these vectors.…”
mentioning
confidence: 99%
“…Ad5 was chosen because in the absence of preexisting immunity (which is the case for most children during the first months of life, when they would be considered primary targets for the vaccine), it is the most immunogenic among several adenoviral vectors tested to date (1,2). Additional adjuvants were avoided in the adenoviral formulation to maintain the immune traits characteristic of the Ad5 vector.…”
Section: Discussionmentioning
confidence: 99%
“…These rare Ad serotypes may have substantial biological differences, likely resulting from specific interactions with blood components or cell receptors (38). We and others have shown that Ad vectors derived from various serotypes differentially interact with naïve and memory T cells (2,27) and human dendritic cells (DCs) (18,28) and are associated with distinct biological effects in vivo (11,17). In this regard, we have recently observed that the formation of immune complexes (ICs) composed of Ad vectors and specific NAbs may have, in addition to reduced transduction efficacy, a differential effect on FcR-expressing cells (29).…”
mentioning
confidence: 95%